2019
DOI: 10.1111/ijn.12760
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to nursing pain management in the emergency department: A qualitative study

Abstract: Background Although pain is a common complaint among patients presenting to emergency departments (EDs), there is a dearth of nursing literature about barriers to pain management. Purpose The study aimed to uncover and understand barriers to pain management in the ED from the registered nurse (RN) perspective. Methods Semistructured interviews were conducted with 12 ED nurses in a Jordanian hospital. Data were collected throughout August 2016. Results Two broad categories with subcategories emerged. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…For instance, some students had a negative clinical experience when a patient's relatives or visitors looked at nurses as housemaids. Earlier research found that some patient relatives and their poor communication with nursing staff affect the work pattern negatively at the ward level (Shoqirat, Mahasneh, Singh, Al Hadid, et al, 2019;Shoqirat, Mahasneh, Singh, Al-Sagarat, et al, 2019). Although nursing worldwide and in Jordan has gained increasing social respect, it seems that students' image has a profound impact on students' first clinical placement and thus, professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some students had a negative clinical experience when a patient's relatives or visitors looked at nurses as housemaids. Earlier research found that some patient relatives and their poor communication with nursing staff affect the work pattern negatively at the ward level (Shoqirat, Mahasneh, Singh, Al Hadid, et al, 2019;Shoqirat, Mahasneh, Singh, Al-Sagarat, et al, 2019). Although nursing worldwide and in Jordan has gained increasing social respect, it seems that students' image has a profound impact on students' first clinical placement and thus, professionalism.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the trusting nurse-patient relationship involving the patient and relative in the care is evident (Aziato & Adejumo, 2015;Rejeh et al, 2008;Shoqirat, 2015;Shoqirat et al, 2019), as also described a key dimension in the FoC framework (Feo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from the literature confirmed that the trusting relationship was essential for pain management, highlighted as a crucial component in the model for PCPM. This relationship was described as based on mutual understanding within the care team, that is providers, patient and relatives, regarding the cause, experience and management of pain (Aziato & Adejumo, 2015;Brown & McCormack, 2006;Dihle et al, 2006;Idvall et al, 2008;Lauzon Clabo, 2008;Rejeh et al, 2008;Shoqirat, 2014Shoqirat, , 2015Shoqirat et al, 2019Shoqirat et al, , 2020Smith et al, 2006). This was achieved when the nurses truly listened to the patient and trusted the experience (Dihle et al, 2006;Idvall et al, 2008;Rejeh et al, 2008;Shoqirat, 2014).…”
Section: Establish and Maintain A Trusting Relationship Including The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses also emphasized the role of environmental factors on pain management. 52 In the study of in the United States, Czarnecki et al referred to inadequate physician prescriptions and low priority of pain management as barriers to pain management in nurses. 53 Pretorius also stated in a study that pain management barriers included unwillingness to prescribe pain relievers, lack of time, heavy workload, and nurses' lack of knowledge of narcotic use, 54 which is consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%